Comorbidity in patients with first-ever ischemic stroke: Disease patterns and their associations with cognitive and physical function - She, Rui; Yan, Zhongrui; Hao, Yanlei; Zhang, Zuoji; Du, Yifeng; Liang, Yajun; Vetrano, Davide L.; Dekker, Joost; Bai, Bo; Lau, Joseph T. F.; Qiu, Chengxuan (Frontiers in Aging Neuroscience, 2022)
The present study examined the prevalence and pattern of comorbidity among Chinese patients with first-ever acute ischemic stroke, and assessed the associations of specific comorbidity patterns with physical and cognitive functioning after stroke occurrence. A hospital-based cross-sectional study was conducted among 2151 patients with first-ever ischemic stroke (age ≥40 years; 64.2% men) who were admitted to two university hospitals in Shandong, China between 2016-2017. Data on demographics, lifestyles, chronic health conditions, and use of medications were collected through in-person interviews, clinical examinations, and laboratory tests. Physical functioning was assessed by the Barthel index (BI) and the modified Rankin Scale (mRS) while cognitive functioning was assessed by the Montreal Cognitive Assessment test. The results showed that comorbidity was present in 90.9% of the stroke patients (women vs. men: 95.2% vs. 88.7%, P<0.001). Exploratory factor analysis identified three patterns of comorbidity, i.e., patterns of degenerative-cardiopulmonary, heart-gastrointestinal-psychiatric, and metabolic-kidney diseases. The number of comorbidities was significantly associated with a higher likelihood of moderate-to-severe physical dependence [odds ratio (95% CI) =1.15 (1.06-1.25) for BI and 1.12 (1.04-1.21) for mRS, all p<0.01] and cognitive impairment [odds ratio (95% CI) =1.11 (1.02-1.20), p=0.017], after adjusting for multiple covariates. Almost all the three comorbidity patterns were associated with increased likelihoods of physical dependence (range for odds ratios: 1.26-1.33) and cognitive impairment (range for odds ratios: 1.25-1.34). No significant association was found between degenerative-cardiopulmonary pattern and mRS. These findings suggest that comorbidity is associated with poor physical and cognitive functioning during the acute phase of ischemic stroke. Routine assessments of comorbidity and cognitive and physical function among patients with acute ischemic stroke should be considered in stroke research and clinical practice.